2008
DOI: 10.2136/sssaj2007.0296
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Reduction by Siderite

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 51 publications
7
52
0
Order By: Relevance
“…6b and c). Cui and Eriksen (1996) (Erdem et al, 2004), U(VI) (Ithurbide et al, 2009;O'Loughlin et al, 2010), nitrite (Rakshit et al, 2008), and selenite (Scheinost et al, 2008). The reaction rate of Cr(VI) with natural siderite increased with decreasing siderite particle size, consistent with heterogeneous reaction (Erdem et al, 2004).…”
Section: Tc(vii) Reduction In Anoxic Sedimentsmentioning
confidence: 61%
See 1 more Smart Citation
“…6b and c). Cui and Eriksen (1996) (Erdem et al, 2004), U(VI) (Ithurbide et al, 2009;O'Loughlin et al, 2010), nitrite (Rakshit et al, 2008), and selenite (Scheinost et al, 2008). The reaction rate of Cr(VI) with natural siderite increased with decreasing siderite particle size, consistent with heterogeneous reaction (Erdem et al, 2004).…”
Section: Tc(vii) Reduction In Anoxic Sedimentsmentioning
confidence: 61%
“…The redox product could be ferrihydrite or goethite with size <8 nm (Janot et al, 1973). Both these oxides have been identified as reaction products of siderite oxidation (Rakshit et al, 2008).…”
Section: Mö Ssbauer Spectroscopymentioning
confidence: 99%
“…Zero-valent metal (Fe 0 , Al 0 ) will remove [5,38,40] nitrates [41][42][43][44][45][46][47][48][49][50][51][52][53][54], nitrites [55,56], bromates [54], chlorates [54], organic compounds (including organo-halides [4][5][6][7]16,[57][58][59][60][61][62][63]) and metals (Ag [64], Al [5], As [40,65,66], Ba [5], Cd [12,64], Co [40], Cr [5,63], Cu [5,42], Fe [5], Hg [64], Mn [5], Ni [42], Pb …”
Section: Space Velocitymentioning
confidence: 99%
“…Literature is available on the impact of vermicompost on growth and productivity of different economically important cash crops in Indian subcontinent as well as from the other parts of the world (Bhattacharjee et al 2001;Rakshit et al 2008;Athani et al 2009;Ansari and Sukhraj, 2010;Joshi and Vig 2010;Lazcano and Dominguez 2010;Theunissen et al 2010;Gupta et al 2011;Tharmaraj et al 2011). Bhattacharjee et al (2001) reported significant increase in both grain and straw yield in upland paddy in Tripura (India) coupled with improvement in soil aggregation, water use efficiency and nutrient uptake in vermicompost treated plots compared to the control and NPK treated plots.…”
Section: Introductionmentioning
confidence: 99%